Morphological characteristics of lenticulostriate arteries in a large age-span population: Results from 7T TOF-MRA - Wei, Ning; Jing, Jing; Zhuo, Yan; Zhang, Zihao (Frontiers in Neurology, 2022)
Lenticulostriate arteries (LSAs) originate from the middle cerebral artery (MCA) and supply blood to the basal ganglia. The evaluation of its structure and function is essential for the etiological diagnosis of subcortical infarction. However, the characteristics of LSA in a healthy population remain poorly described. Our study aims to acquire morphological measurements of LSA by 7T TOF-MRA on 140 healthy volunteers with a large age range (21~68). The results showed that the number of branches of LSA gradually decreases with age (r=-0.328, p<0.001), and the maximum visible length becomes shorter (r=-0.385, p<0.001). Moreover, there is a significant correlation between the volume of the basal ganglia nuclei and the morphology of LSA. The volume of putamen was associated with the number of stems (r=0.273, p<0.001) and branches (r=0.248, p<0.001) of LSAs, while the volume of caudate was closely related to the maximum visible length of LSAs (r=0.200, p=0.001). In conclusion, this study was the first in-vivo study to report the morphology of LSA with a large sample size of more than one hundred cases. These findings are valuable in understanding the degeneration of LSAs during aging.